Point-of-care tests for infectious diseases: Barriers to implementation across three London teaching hospitals - Bustinduy, A; Jeyaratnam, D; Douthwaite, S; Tonkin-Crine, S; Shaw, R; Hyrapetian, L; Sevdalis, N; Goldenberg, S; Adams, E; Sharland, M; CLAHRC South London Paediatric Infection Network, (Wiley, 2017)
Existing Point-of-care tests (POCT) to help identify infection-related causes of illness can complement diagnostic and disposition decisions in children attending emergency departments.(1) Evidence-based clinical algorithms can integrate such POCT to aid in the admission and discharge decision process. Paediatric studies validating these tools are scarce, with very few studies conducted in UK centres.(2-5) POCT can be based on host infection markers (e.g. finger prick tests for C-reactive protein (CRP) to help decide if the patient has a bacterial or viral infection) or pathogen detection tests (e.g. throat/nose swabs to rapidly diagnose viral infections such as RSV or influenza). This article is protected by copyright. All rights reserved.